Peranan Advokat sebagai Penegak Hukum - Melinna Anggraini; Mutiara Sachputri; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Advocate is a law enforcement and a free, independent and responsible job in enforcing the law guaranteed by law. It means that lawyers have rights, obligations and responsibilities in accordance with the rules of law advocates. According to Law No. 18 Year 2003 concerning Advocates, insisted that, Advocate is a person who is providing legal services both inside and outside the court. Legal services in question are services rendered in the form of lawyers providing legal advice, legal assistance, exercise the power, represent, assist, defend and perform other legal actions in the interests of the client. Keywords : Law Enforcement, Advocate, Court, Legal Advice.